Psychological characteristics of religious delusions - Iyassu, R; Jolley, S; Bebbington, P; Dunn, G; Emsley, R; Freeman, D; Fowler, D; Hardy, A; Waller, H; Kuipers, E; Garety, P (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2014)
Purpose: Religious delusions are common and are considered to be particularly difficult to treat. In this study we investigated what psychological processes may underlie the reported treatment resistance. In particular, we focused on the perceptual, cognitive, affective and behavioural mechanisms held to maintain delusions in cognitive models of psychosis, as these form the key treatment targets in cognitive behavioural therapy. We compared religious delusions to delusions with other content. Methods: Comprehensive measures of symptoms and psychological processes were completed by 383 adult participants with delusions and a schizophrenia spectrum diagnosis, drawn from two large studies of cognitive behavioural therapy for psychosis. Results: Binary logistic regression showed that religious delusions were associated with higher levels of grandiosity (OR 7.5; 95 % CI 3.9-14.1), passivity experiences, having internal evidence for their delusion (anomalous experiences or mood states), and being willing to consider alternatives to their delusion (95 % CI for ORs 1.1-8.6). Levels of negative symptoms were lower. No differences were found in delusional conviction, insight or attitudes towards treatment. Conclusions: Levels of positive symptoms, particularly anomalous experiences and grandiosity, were high, and may contribute to symptom persistence. However, contrary to previous reports, we found no evidence that people with religious delusions would be less likely to engage in any form of help. Higher levels of flexibility may make them particularly amenable to cognitive behavioural approaches, but particular care should be taken to preserve self-esteem and valued aspects of beliefs and experiences. © 2013 Springer-Verlag Berlin Heidelberg.